The role of educational managers in the successful implementation of Life Skills programmes in FET Colleges - Steyn, Isabel Suzanne (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPhil (Industrial Psychology))--University of Stellenbosch, 2006.